2021
DOI: 10.1080/14760584.2021.1882309
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of malaria vaccine efficacy

Abstract: Introduction: An effective vaccine against malaria forms a global health priority. Both naturally acquired immunity and sterile protection induced by irradiated sporozoite immunization were described decades ago. Still no vaccine exists that sufficiently protects children in endemic areas. Identifying immunological correlates of vaccine efficacy can inform rational vaccine design and potentially accelerate clinical development.Areas covered: We discuss recent research on immunological correlates of malaria vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 222 publications
0
18
0
Order By: Relevance
“…WSp vaccines primarily aim at boosting the host’s immunity through the generation of effective and long-lasting immune responses that control and/or eliminate the parasite during the pre-erythrocytic stage of its life cycle. The investigation of these immunological mechanisms and their correlation with protection have been the focus of multiple studies that led to a thorough, yet still incomplete, picture of the immunity that ensues following vaccination, as recently reviewed ( 134 136 ). Although several studies have suggested a relation between some immune parameters and protection, a definitive immune correlate of protective efficacy of WSp vaccination remains to be clearly identified.…”
Section: Immune Responses Elicited By Whole-sporozoite Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…WSp vaccines primarily aim at boosting the host’s immunity through the generation of effective and long-lasting immune responses that control and/or eliminate the parasite during the pre-erythrocytic stage of its life cycle. The investigation of these immunological mechanisms and their correlation with protection have been the focus of multiple studies that led to a thorough, yet still incomplete, picture of the immunity that ensues following vaccination, as recently reviewed ( 134 136 ). Although several studies have suggested a relation between some immune parameters and protection, a definitive immune correlate of protective efficacy of WSp vaccination remains to be clearly identified.…”
Section: Immune Responses Elicited By Whole-sporozoite Vaccinationmentioning
confidence: 99%
“…Vaccines commonly act by inducing an antibody-mediated response against specific microorganisms or their constituents. The humoral responses induced by WSp vaccines are largely directed at pre-erythrocytic antigens, with CSP, the most abundant protein on the surface of sporozoites, representing the hallmark parasite target [reviewed in ( 134 , 136 , 138 , 139 )]. Sporozoite- or CSP-specific antibodies are consistently induced in response to WSp vaccination of malaria-naïve individuals, and some studies have reported a correlation of antibody titers with RAS ( 47 , 69 ), CPS ( 115 ), GAP ( 92 ) or PbVac ( 130 ) immunization doses, or with PfSPZ-induced protection ( 48 , 92 ).…”
Section: Immune Responses Elicited By Whole-sporozoite Vaccinationmentioning
confidence: 99%
“…Recent studies have shown that Plasmodiumspecific CD8 + tissue-resident memory (T RM ) cells in the liver contribute to protective immunity against malaria [6], resulting in a focus on the development of novel vaccination strategies to maximize T RM generation in the liver for a more effective malaria vaccine. A clear understanding of what constitutes a protective immune response against the different life-cycle stages will also enable the identification of immunological correlates of vaccine efficacy which may help to accelerate clinical vaccine development [7]. Recent studies [7] suggest that functional assays that represent in vivo antiparasite effector mechanisms, may be a better predictor of protective immunity than many of the simple quantitative assays that have been employed to date.…”
Section: Biological Strategies and Political Hurdles In Developing Malaria Vaccinesmentioning
confidence: 99%
“…A clear understanding of what constitutes a protective immune response against the different life-cycle stages will also enable the identification of immunological correlates of vaccine efficacy which may help to accelerate clinical vaccine development [7]. Recent studies [7] suggest that functional assays that represent in vivo antiparasite effector mechanisms, may be a better predictor of protective immunity than many of the simple quantitative assays that have been employed to date.…”
Section: Biological Strategies and Political Hurdles In Developing Malaria Vaccinesmentioning
confidence: 99%
“…Exploring the preimmunization correlates of protection in malaria vaccine trials presents an opportunity to identify the immunological conditions that set the stage for vaccine-induced responses that are protective against future infection and to help guide the rational design of more effective vaccines. While the list of studies in this research area is not extensive, some preimmunization correlates of protection have been identified for vaccines against influenza [6][7][8][9] , hepatitis B [10][11][12] , yellow fever 13 and malaria [14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%